Effect of the extract of Annona muricata and Petunia nyctaginiflora on Herpes simplex virus - Padma P.; Pramod N.P.; Thyagarajan S.P.; Khosa R.L. (My University, 2025)
Annona muricata (Annonaceae) and Petunia nyctaginiflora (Solanaceae) were screened for their activity against Herpes simplex virus-1 (HSV-1) and clinical isolate (obtained from the human keratitis lesion). We have looked at the ability of extract(s) to inhibit the cytopathic effect of HSV-1 on vero cells as indicative of anti-HSV-1 potential. The minimum inhibitory concentration of ethanolic extract of A. muricata and aqueous extract of P. nyctaginiflora was found to be 1 mg/ml.